Analisis Kinerja Belanja Dalam Laporan Realisasi Anggaran Pada Dinas Energi Dan Sumber Daya Mineral Provinsi Kalimantan Timur - Rina Masithoh Haryadi, Erisandi Saputra Imam Nazarudin Latif (EKONOMIA, 2020)
The purpose of this study is to seek the spending execution at the Department of Energy and Mineral Resources of the Province of East Kalimantan in the 2015-2018 fiscal year can be said to be good in terms of the analysis of expenditure variance, analysis of expenditure growth, analysis of expenditure harmony, and the ratio of expenditure efficiency.Background theory used in this research is theoretical foundation concerning public sector accounting, budget implementation reports, and expenses execution.The instrument used is the analysis of shopping performance consisting of an analysis of shopping variants, an analysis of expenditure growth, an analysis of expenditure harmony and a ratio of expenditure efficiency.The results of the analysis presented is, a. The expenses execution in terms of analysis of expenditure variance can be said to be good because the implementation of spending is smaller than the budget, b. Expenses execution in terms of an analysis of expenditure growth cannot be said to be positive because in 2017 and 2018 the number of expenditure was decreased and resulting negative, c. The expenses execution in terms of analysis of the harmony of spending is more dominant operational expenditure than ‘modal’ expenditure because operational expenditure is up to 90% above of total expenditure while ‘modal’ expenditure is less than 10% of total expenditure, d. The expenses execution in terms of the expenses efficiency ratio can be said to be efficient because the criteria showed the result are below 100%.